1991
DOI: 10.1007/bf01326618
|View full text |Cite
|
Sign up to set email alerts
|

Moving beyond women's career choices: Factors associated with career continuity among female former art students

Abstract: In 1987, Betz and Fitzgerald identified four general categories (individual, educational, background and adult lifestyle) and 17 specific components therein that facilitated women's career choices. They noted, for instance, that a combination of variables such as high ability and high self esteem (individual), as well as a working mother and early work experience (background), higher education (educational) combined with no marriage and no or few children (adult lifestyle), constituted several of the critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…6 Within the small set of empirical studies on artists exists an even smaller set of studies on artists' employment decisions. The employment decision of an artist has typically been modeled as an input to other types of labor outcomes, such as earnings (Wassall & Alper, 1992), occupational persistence (Stohs, 1991a(Stohs, , 1991b, and work hours (Robinson & Montgomery, 2000) via a traditional labor supply model. In general, these studies have found that not only is there great variability in artists' incomes, but also that the return on education is lower than in other occupations with otherwise similar characteristics (Filer, 1990).…”
Section: Artists and Self-employment Determinantsmentioning
confidence: 99%
“…6 Within the small set of empirical studies on artists exists an even smaller set of studies on artists' employment decisions. The employment decision of an artist has typically been modeled as an input to other types of labor outcomes, such as earnings (Wassall & Alper, 1992), occupational persistence (Stohs, 1991a(Stohs, , 1991b, and work hours (Robinson & Montgomery, 2000) via a traditional labor supply model. In general, these studies have found that not only is there great variability in artists' incomes, but also that the return on education is lower than in other occupations with otherwise similar characteristics (Filer, 1990).…”
Section: Artists and Self-employment Determinantsmentioning
confidence: 99%
“…In the former study, he developed predictions of the first, best, and last contributions based on individual differences and contrasts across scientific disciplines. The correlates of whether artists' careers were continuous or interrupted during 18 years following art school were studied by Stohs (1991). She found large gender differences in continuity (women had more interrupted careers) and that, among women, several background indicators (e.g., mother's job) and adult life-style indicators (e.g., number of children, number of exhibits) did discriminate.…”
Section: Job Transitionsmentioning
confidence: 98%